Pendudukan Jepang di Pontianak, 1941-1943 - Yafi, Reyhan Ainun; Darmadi, Yusri (Warisan: Journal of History and Cultural Heritage, 2023)
This study aims to analyze whether the socio-economic conditions of Pontianak people at the time of the arrival of Japanese troops were a factor in their unpreparedness to face attacks. The method used in this study is the historical method. The sources used were newspapers, among others, West Borneo Shimbun, Akcaya Daily, and Evening Post. The results showed that Pontianak society at the beginning of the arrival of the Japanese was very diverse in terms of war preparedness. Some of the residents of Pontianak City at that time were traders. They were busy trading and were unaware of the changing political situation of Asia in general and the Dutch East Indies in particular. The Japanese landing in Pontianak caused the destruction of the social and economic infrastructure of trade due to the mistakes of the Japanese army in dropping bombs on target targets. However, the destruction was also triggered by the lack of preparation of the Dutch colonial government for the arrival of Japanese troops in Pontianak.